Smoking influences the occurrence of radiodermatitis in head and neck-irradiated patients - Caetano, Rafael D. S.; Volpato, Luiz E. R.; Castro, Paulo H. D. S.; Borba, Alexandre M.; Aranha, Andreza M. F.; Kuga, Milton C. [UNESP]; Tonetto, Mateus R.; Soares, Ana C.; Bandeca, Matheus C.; Borges, Álvaro H. (Jaypee Brothers Medical Publishing, 2017)
Introduction: This study aimed to evaluate the occurrence of radiodermatitis in patients undergoing radiotherapy in the head and neck. Materials and methods: Thirty-eight patients were evaluated 6 months after the end of radiotherapy to treat cancer in the head and neck region. The radiodermatitis was clinically classified as absent, acute, or chronic. Data, such as age, sex, race/color, drinking and smoking habits, number of radiotherapy sessions, and conduction of adjuvant chemotherapy were also obtained. Fisher’s exact test and Pearson’s test were used to analyze the correlation of the independent variables and the presence of radiodermatitis. Results: The mean age of the patients was 59.71 (± 10.67), and 29 (76.3%) were men, 24 (63.2%) were non-white race/color, 28 (63.7%) were alcohol consumers, and 33 (86.8%) were smokers. The average number of radiotherapy sessions was 37.26 (± 7.66); 30 (78.9%) patients underwent chemotherapy; and 26 (68.4%) had chronic radiodermatitis. The only variable statistically related to the occurrence of radiodermatitis in the patients was smoking. Conclusion: Radiodermatite was quite prevalent among the studied patients and was directly related to the smoking habit.
Keywords: Head and neck neoplasms; Radiodermatitis; Radiotherapy; Smoking